The Effectiveness of Edugame Based Learning to Improve Skills and Critical Thinking in SD Negeri Labuhan 1 Sereseh Students - Ary Wijaya; Nuril Huda; Muhajir Muhajir (International Forum of Researchers and Lecturers, 2025)
Game-Based Learning (GBL) has emerged as an innovative learning approach aimed at enhancing student engagement and promoting the development of critical thinking skills, particularly at the elementary school level. This study was conducted at SD Negeri Labuhan 1 using a qualitative approach and a case study method. The primary objective of this research is to analyze the implementation of GBL within the context of elementary education, focusing on students’ and teachers’ needs and interests, the strategies used for implementation, the impact of GBL on students’ critical thinking skills, and the supporting and inhibiting factors affecting its success. The findings indicate that 75% of students expressed a higher preference for game-based learning over conventional teaching methods, showing high levels of enthusiasm and participation during the learning process. GBL proved effective in increasing students' motivation to learn, strengthening collaboration, and stimulating analytical and reflective thinking. However, several challenges were encountered in the implementation of GBL, including limited technological infrastructure in schools and the lack of specialized training for teachers in designing and managing game-based learning activities effectively. Based on these findings, it can be concluded that GBL holds significant potential as a teaching strategy that can foster students’ critical thinking skills from an early age. Nevertheless, to achieve optimal outcomes, strong support from various stakeholders is essential, including the provision of adequate facilities and the enhancement of teachers’ competencies through continuous professional development and training in designing and applying GBL in daily classroom activities.